Contribution of Baroreceptor Function to Pain Perception and Perioperative Outcomes. (April 2019) - Suarez-Roca, Heberto; Klinger, Rebecca Y.; Podgoreanu, Mihai V.; Ji, Ru-Rong; Sigurdsson, Martin I.; Waldron, Nathan; Mathew, Joseph P.; Maixner, William
Abstract : Baroreceptors are mechanosensitive elements of the peripheral nervous system that maintain homeostasis by coordinating physiologic responses to external and internal stimuli. While it is recognized that carotid and cardiopulmonary baroreceptor reflexes modulate autonomic output to mitigate excessive fluctuations in arterial blood pressure and to maintain intravascular volume, increasing evidence suggests that baroreflex pathways also project to key regions of the central nervous system that regulate somatosensory, somatomotor, and central nervous system arousal. In addition to maintaining autonomic homeostasis, baroreceptor activity modulates the perception of pain, as well as neuroimmune, neuroendocrine, and cognitive responses to physical and psychologic stressors. This review summarizes the role that baroreceptor pathways play in modulating acute and chronic pain perception. The contribution of baroreceptor function to postoperative outcomes is also presented. Finally, methods that enhance baroreceptor function, which hold promise in improving postoperative and pain management outcomes, are presented. Abstract : The authors discuss the evidence that baroreceptor function modulates acute and chronic pain perception and contributes to perioperative outcomes. As such, these little-studied associations represent an opportunity to investigate a novel process that impacts: (1) the understanding of physiologic factors that mediate chronic pain and perioperative outcomes and (2) the novel interventions that will improve pain management and perioperative outcomes.Supplemental Digital Content is available in the text.